Pengaruh Kompensasi Dan Budaya Organisasi Terhadap Loyalitas Karyawan Pada PT. Tiki Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2024)
ABSTRACT This study aims to determine the effect of compensation and organizational culture on employee loyalty at PT. Tiki Palembang. The method used in this study is a quantitative method with the number of samples studied is 70 employees. The data analysis technique used in this research is simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and f test using the software program spss 22 for windows. From the results of the partial t-test research, it shows that there is an effect of compensation (X1) with a significant value of 0.000